Statistical Analysis of the Financial Solvency of the Russian Arctic Regions - A. N. Chapargina; N. V. Dyadik; А. Н. Чапаргина; Н. В. Дядик (Voprosy statistiki, 2021)
The uneven distribution of natural resources on the territory of Russia and the limited ﬁnancial capabilities of the regions of the Russian Federation to exercising their powers, according to the authors, predetermine the relevance of considering the problem of assessing ﬁnancial solvency for each region. The Arctic zone of the Russian Federation as a management object is nowadays an issue of concern from researchers and requires special attention since most of the country’s resource potential is concentrated on its territory. The study aims at a statistical assessment of the ﬁnancial viability of the regions of the Russian Arctic through a correlation analysis aimed at exploring the forms of linking indicators that allow us to identify common and speciﬁc features of their regional development.The article substantiates the system of statistical indicators that directly or indirectly characterize the ﬁnancial solvency of the regions. The analysis of the ﬁnancial solvency of the regions according to the official statistics for the period from 2005 to 2018 was carried out sequentially and in stages: 1st stage - selection of the data array; 2nd stage - formation of a case of ﬁnancial indicators; 3rd stage - building a matrix for correlation analysis; 4th stage - correlation analysis; 5th stage - interpretation of the results.Using the method of correlation analysis, the authors constructed a matrix of correlation pairs, identifying the most relevant ones for assessing the ﬁnancial solvency of the region. Comparative analysis of paired correlation coefficients for the Arctic regions made it possible to assess the relationship between certain directions and features of their development.Assessment of the ﬁnancial independence of the constituent entities is the central problem of balancing regional budgets. In this regard, the results of the study may be of interest to regional and federal authorities for forecasting and strategic planning of the development of the Arctic regions in the face of limited ﬁnancial ...